Epilepsy with auditory features: A heterogeneous clinico-molecular disease. (June 2015) - Pippucci, Tommaso; Licchetta, Laura; Baldassari, Sara; Palombo, Flavia; Menghi, Veronica; D'Aurizio, Romina; Leta, Chiara; Stipa, Carlotta; Boero, Giovanni; d'Orsi, Giuseppe; Magi, Alberto; Scheffer, Ingrid; et al.
Abstract : Objective: To identify novel genes implicated in epilepsy with auditory features (EAF) in phenotypically heterogeneous families with unknown molecular basis. Methods: We identified 15 probands with EAF in whom an LGI1 mutation had been excluded. We performed electroclinical phenotyping on all probands and available affected relatives. We used whole-exome sequencing (WES) in 20 individuals with EAF (including all the probands and 5 relatives) to identify single nucleotide variants, small insertions/deletions, and copy number variants. Results: WES revealed likely pathogenic variants in genes that had not been previously associated with EAF: a CNTNAP2 intragenic deletion, 2 truncating mutations of DEPDC5, and a missense SCN1A change. Conclusions: EAF is a clinically and molecularly heterogeneous disease. The association of EAF with CNTNAP2, DEPDC5, and SCN1A mutations widens the phenotypic spectrum related to these genes. CNTNAP2 encodes CASPR2, a member of the voltage-gated potassium channel complex in which LGI1 plays a role. The finding of a CNTNAP2 deletion emphasizes the importance of this complex in EAF and shows biological convergence.